Effectiveness of social problem solving model in improving social skills of transvestites in the special regions Yogyakarta - Aman Aman; Ajat Sudrajat; Lia Yuliana (Journal of Social Studies (JSS), 2018)
This study aims to find out: the effectiveness of character education models in improving social skills for transvestites in Yogyakarta Special Region. This research uses Research and Development method which consists of four stages, namely: (1) preliminary stage, (2) the planning stage of character education models for transgender as the development of the initial product form, (3) the testing, evaluation and revision stages through practical learning improvement of social skills, and (4) implementation phase. The number of transsexuals who were sampled in the one-on-one trial in 2015 was 5 transvestites selected by purposive sampling. In the second year the trial was expanded to 1 management of Kebaya Shelter house and involved 22 transvestites. Whereas field operational trials were conducted on 32 transvestites in Kebaya and Iwayo. Data collection techniques use FGD techniques, questionnaires, interviews, observation, and documentation techniques. Data validity uses expert validation, while the validity of qualitative data with source triangulation techniques, theory and methods. Quantitative data analysis with descriptive analysis techniques and qualitative data with interactive models. The results showed that: Field operational trials of 32 transvestites, it can be seen that there was an increase in transvestites' social skills after training the character education model of SPS models for waria. The pretest results showed a good average classification with a mean of 3.20. While the posttest results indicate an increase to a good classification with a mean of 3.58. Based on these data shows that all aspects that are considered good regarding social skills show a good and good classification.  Keywords: Problem Solving, social skills, of transvestites